2003
DOI: 10.1063/1.1536980
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between electronic and molecular structure distortions and vibrational properties. II. Amide I modes of NMA–nD2O complexes

Abstract: Hydration effects on the molecular structure and amide I mode frequency of a prototype peptide molecule, N-methylacetamide (NMA), when it is solvated by a few water molecules, were investigated by carrying out ab initio calculations for a number of NMA–water complexes. The harmonic frequency shift of the amide I mode in NMA–nD2O (n=1–5) complex was found to originate from the combination of the molecular cubic anharmonicity and displacement of the amide I coordinate when the NMA is hydrated. Using a multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
275
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 247 publications
(290 citation statements)
references
References 34 publications
8
275
0
6
Order By: Relevance
“…Other research groups have shown this and have correlated the shift to solvent electric field or bond length effects at the CdO, which has been developed to an empirical FF correction. 78,79 For our uncorrected DFT calculations, some patterns have emerged around these computed amide I′ frequencies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other research groups have shown this and have correlated the shift to solvent electric field or bond length effects at the CdO, which has been developed to an empirical FF correction. 78,79 For our uncorrected DFT calculations, some patterns have emerged around these computed amide I′ frequencies.…”
Section: Discussionmentioning
confidence: 93%
“…The frequency is known to correlate to the CdO bond length in amides. 76,[78][79][80] The effect of the 6-31++G** basis set on the 2 × 13 r 2 × 3 transfer is shown in Figure 6e,f. Again, since it is a 2 × 3-based transfer, the large and small ring coupling constants are roughly equal, with ∆ω ∼ 8 cm -1 , out-of-phase to higher frequency, and ∆ω ∼ 7 cm -1 , opposite sign splitting, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure is an extension to the one applied previously for the amide I band in polypeptides. [20][21][22][23][24][25] The reconstruction method also produces values for shifts in the harmonic frequency of the oscillators due to the peptide environment, which are included in the parameters ω ni . For the anharmonic shifts we accepted the values deduced from experiments on NMA (16 cm -1 for amide I (ref 6) and 11 cm -1 for amide II (ref 4)).…”
Section: Modeling Vibrational Energy Transportmentioning
confidence: 99%
“…A computationally inexpensive way of including solvent effects on the amide I frequencies is to parametrize ab initio calculations of N-methylacetamide (NMA) and water clusters. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] This method exploits the linear correlation found between the C=O bond length, stretching frequency and electrostatic potential at the atoms of NMA, 18,31,32 which provides a link between perturbation of molecular (and electronic) structure by the electric field of the solvent and the resulting shift of the vibrational frequency. Parametrized electrostatic calculations using the building block approach have been used in protein amide I sim-ulations of ubiquitin, 10,33 other proteins 34 as well as polypeptides in membrane environment.…”
Section: Introductionmentioning
confidence: 99%